Droplet impingement on coated incline heated surface - Nai, Ze Yuan (Nanyang Technological University, 2024)
The investigation into the hydrodynamic phenomena of droplet impact on inclined heated surfaces has garnered significant interest, driving extensive research efforts. Advances in surface engineering, propelled by modern technology, have facilitated the development of surfaces with diverse properties. While modified surfaces show promise in addressing engineering challenges associated with droplet impingement, research in this area, particularly concerning the phase change associated with boiling, remains relatively limited. This study focuses on analyzing the hydrodynamic behavior of droplets impacting inclined surfaces coated with nanoparticles and subjected to heating. Experimental observations and theoretical insights into water droplet impingement on coated and heated inclined surfaces are presented. Experimental observations reveal variations in droplet behavior across different setups, with an increasing standard deviation of the Weber number as height increases. Additionally, at higher temperatures, the maximum spreading diameter changes as droplets tend to evaporate upon impingement. Two types of modified heating surfaces, hydrophilic and superhydrophobic, are employed in the experiments, with temperatures ranging from 25°C to 300°C. Across the different inclined surfaces, the spreading factor of droplets exhibits a significant increase, showing an upward trend with increasing Weber numbers, accompanied by distinct hydrodynamic behaviors. On hydrophilic inclined surfaces, droplets display a sequence of behaviors including sticking, stick and spread, spread boil, rebounding with boiling, breakup with splashing, rebounding, and rebounding with breakup, across all Weber numbers. Conversely, droplets on superhydrophobic surfaces experience splashing and rebounding with breakup at low Weber numbers and rebound at high Weber numbers. A unique hydrodynamic behavior is observed on a 30° inclined superhydrophobic surface, where droplets slide off upon impingement. The spreading factors across low-incline surfaces exhibit clustering, while high-incline surfaces display a scattered graph. Future research avenues include exploring variations in surface patterns and wettability modifications, leveraging technological advancements to deepen our understanding in this field.